Lake Restoration Handbook A New Zealand Perspective (Springer International Publishing, 2018)
Lakes across the globe require help. The Lake Restoration Handbook: A New Zealand Perspective addresses this need through a series of chapters that draw on recent advances in modelling and monitoring tools, citizen science and First Peoples' roles, catchment and lake-focused restoration techniques, and policy implementation. New Zealand lakes, like lakes across the globe, are subject to multiple pressures that have increased in severity and scale as land use has intensified, invasive species have spread and global climate change becomes manifest. This books builds on the popular Lake Managers Handbook (1987), which provided guidance on undertaking investigations into, and understanding lake ecosystems in New Zealand. The Lake Restoration Handbook: A New Zealand Perspective synthesises contemporary issues related to lake restoration and rehabilitation, integrated with social science and cultural viewpoints, and complemented by authoritative topic-area summaries by renowned scientists and practitioners from across the globe. The book examines the progress of lake restoration and the new and emerging tools available to managers for predicting and effecting change. The book will be a valuable resource for natural and social scientists, policy writers, lake managers, and anyone interested in the health of lake ecosystems.